RELIGI PADA MASA KERAJAAN SUNDA KAWALI (TELAAH ATAS PRASASTI PENDEK DI SITUS ASTANA GEDE, KAWALI) - Saptono, Nanang (Berkala Arkeologi, 1994)
This article contains a study of the Astana Gede located in Dusun Indrayasa, Desa Kawali, Kecamatan Kawali, Kabupaten Ciamis, Jawa Barat. This site is known as the Kingdom of Sunda former capital. On this site there are some archaeological data, including inscriptions in Old Sundanese language. The archaeological data that attracts the interest of many experts are several inscriptions and several stuctures characterized by megalithic culture. The existence of inscription in the form of standing stones is associated with indigenous religion related to megalithic culture. The megalithic tradition thrives alongside with the Hinduism and Buddhism in the Kingdom of Sunda.